Choosing an antianginal therapy strategy in patients with stable coronary artery disease in real clinical practice: the advantages of trimetazidine - E. V. Borisova; O. D. Ostroumova; A. P. Pereverzev; E. E. Pavleeva (Медицинский совет, 2021)
Cardiovascular diseases (CVD) are the leading cause of death among adults worldwide, including in the Russian Federation. At the same time, the leading position in the structure of causes of death from CVD is occupied by coronary heart disease (CHD) (16% of the total number of deaths in the world per year). The new clinical guidelines of the Ministry of Health of the Russian Federation for the management of patients with stable coronary heart disease in 2020 identify two main goals of conservative therapy – the elimination of symptoms of the disease and the prevention of cardiovascular complications (CVD). In this connection, when choosing antianginal therapy in patients with stable angina, it is necessary to consider the possibility of using combinations of both first-line and second-line drugs in order to really improve the effectiveness of treatment and achieve the goals set. It is advisable and justified to use more widely 2-line drugs, in particular trimetazidine, at any stage of therapy to enhance the antianginal effectiveness of b-blockers, calcium antagonists and prolonged-acting nitrates, especially in patients with hemodynamic features (arterial hypotension, rhythm and conduction disorders), which is demonstrated in the given clinical example. The effective addition of tremetazidine to the arsenal of traditional antianginal drugs is legislated in practice and is reflected in the new clinical recommendations of the Ministry of Health of the Russian Federation in 2020. The accumulated experience of using trimetazidine allows a pathogenetically sound approach to the treatment of stable CHD, restoring the balance between the need and delivery of oxygen to the heart muscle, and the safety profile expands the possibilities of use in patients with comorbid pathology.